Stingless bee Trigona spinipes (Hymenoptera: Apidae) behavior on chayote flowers (Sechium edule) - Malerbo-Souza, Darclet Teresinha; Costa, Carlos Frederico Silva da; Pimentel, André Carlos Silva; Andrade, Milena Oliveira de; Siqueira, Rodrigo Alves de; Silva, Robin César Barros da; Souza, Camila Malerbo de; Souza, Felipe Gusmão de (Acta Scientiarum. Animal Sciences, 2022)
This experiment aimed to evaluate the forage species and their effect on fruit production of the chayote crop. For this, the culture was under observation in the first ten minutes at each time, from 7:00 am to 6:00 pm, with three repetitions, in each year studied (1994, 2001, 2009 and 2016). With the exception of 2009, Trigona spinipes stingless bees were frequent and constant insects in these flowers between 8:00 am and 1:00 pm, visiting mainly male flowers for nectar collection and due to foraging behavior this stingless bee may be considered a pollinator of the chayote.